Enhancing Learning Interest in Indonesian Language Through Language Games: A Classroom Action Research Study Among First-Grade Elementary Students - Muhammad Ardani; Sutikno; Rahmat Kartolo (International Journal of Educational Research Excellence, 2026)
This research was motivated by the low level of interest in learning Indonesian among first-grade students at SD Negeri 087 Panyabungan. Students tended to be passive, lacked enthusiasm, and were easily distracted during lessons. The conventional teaching methods used by the teacher did not align with the learning characteristics of young children, who typically enjoy play-based activities. Therefore, this study aimed to enhance students’ interest in learning Indonesian through the implementation of language game strategies. This research employed a qualitative approach in the form of Classroom Action Research (CAR) conducted in two cycles. The research subjects were 19 first-grade students at SD Negeri 087 Panyabungan. Data were collected through observation, interviews, and documentation, and then analyzed using both qualitative and quantitative techniques. The results showed a significant increase in students’ learning interest. Before the intervention, only 35.98% of students demonstrated learning interest, with an average score of 1.84. After implementing language games in Cycle I, this figure increased to 49.2% with an average score of 2.53. A further improvement was recorded in Cycle II, reaching 75.97% with an average score of 3.37. The percentage of students showing a positive learning attitude also rose from 52.63% (pre-action) to 84.21% in Cycle II. In addition, the learning success rate improved from 30% (pre-action) to 78.94% in Cycle II. Games such as “Name Hunt” and activities using modeling clay (plastisin) proved effective in enhancing student engagement, creativity, and self-expression. This strategy fostered a joyful and participatory learning atmosphere, well-suited to the imaginative and motor-active nature of early childhood learners. It can be concluded that the use of language games is an effective strategy for increasing interest in learning Indonesian among first-grade elementary students.